2015
DOI: 10.1089/scd.2014.0137
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Aneuploidy in Mesenchymal Stromal Cells Detected by In Situ Karyotyping and Fluorescence In Situ Hybridization: Suggestions for Reference Values for Stem Cells

Abstract: Cytogenetic testing is important to ensure patient safety before therapeutic application of mesenchymal stromal cells (MSCs). However, the standardized methods and criteria for the screening of chromosomal abnormalities of MSCs have not yet been determined. We investigated the frequency of cytogenetic aberrations in MSCs using G-banding and fluorescence in situ hybridization (FISH) and suggest reference values for aneuploidy in MSCs. Cytogenetic analysis was performed on 103 consecutive cultures from 68 MSCs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Asymmetric aneuploidy has been found to be prevalent in malignant hematologic diseases, but it remains unclear whether these aneuploid MSPC clones represent senescent or transformed cells [ 639 ]. MSPCs from patients with acute lymphoblastic leukemia demonstrated leukemia-associated chromosomal translocations in 10 of 10 patients’ samples analyzed, with proportions of translocation-positive MSPCs varying from 10% to 54% [ 640 ].…”
Section: Mspcs In Mds and Aml: Clone-derived Or Clone-induced?mentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric aneuploidy has been found to be prevalent in malignant hematologic diseases, but it remains unclear whether these aneuploid MSPC clones represent senescent or transformed cells [ 639 ]. MSPCs from patients with acute lymphoblastic leukemia demonstrated leukemia-associated chromosomal translocations in 10 of 10 patients’ samples analyzed, with proportions of translocation-positive MSPCs varying from 10% to 54% [ 640 ].…”
Section: Mspcs In Mds and Aml: Clone-derived Or Clone-induced?mentioning
confidence: 99%
“…The concept of a common origin has recently also been supported by the observation that chromosomal aberrations mirroring those found in the corresponding leukemic blasts (in addition to distinct additional cytogenetic aberrations) were detected in AML-MSPCs in some AML patients [ 324 ]. Discrepant findings in the literature regarding the clonality of MSPCs may result from a lack of standardized methods for the screening of chromosomal abnormalities of MSPCs as well as the lack of harmonization of MSPC-purifying strategies, but also from the varying culture periods, different numbers of passages, and different tissue culture media used to grow cells prior to cytogenetic analyses [ 324 , 639 , 641 ].…”
Section: Mspcs In Mds and Aml: Clone-derived Or Clone-induced?mentioning
confidence: 99%
“…However, the occurrence of karyotypic instability in cultured hBM-MSCs has been documented. It has been admitted that genome instability enables tumor cells to acquire their characteristics [ 11 ], therefore the tumorigenesis potential of the hMSCs has become the most important concern for clinical use of MSCs [ 12 ]. Though, hBM-MSC studies presented highly conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…ND, not detected; ns, not significant stable during culturing in vitro [42][43][44][45][46][47][48]. On the contrary, abundant recent studies have revealed that human MSCs exhibited spontaneous genomic alternation with increased passage number [49][50][51][52][53][54]. Previous chromosomal profiling studies also provide that karyotypical abnormalities and chromosomal instability in early passaged human MSCs disappear during the extended passage [51,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%